In vitro chipping behaviour of all-ceramic crowns with a zirconia framework and feldspathic veneering: comparison of CAD/CAM-produced veneer with manually layered veneer - Schmitter, Marc; Müller, Denise; Rues, Stefan (Journal of oral rehabilitation, 2013)
The purpose of this in vitro study was to assess the breaking load of zirconia-based crowns veneered with either CAD/CAM-produced or manually layered feldspathic ceramic. Thirty-two identical zirconia frameworks (Sirona inCoris ZI, mono L F1), 0·6 mm thick with an anatomically shaped occlusal area, were constructed (Sirona inLab 3.80). Sixteen of the crowns were then veneered by the use of CAD/CAM-fabricated feldspathic ceramic (CEREC Bloc, Sirona) and 16 by the use of hand-layered ceramic. The CAD/CAM-manufactured veneer was attached to the frameworks by the use of Panavia 2.0 (Kuraray). Half of the specimens were loaded until failure without artificial ageing; the other half of the specimens underwent thermal cycling and cyclic loading (1·2 million chewing cycles, force magnitude Fmax = 108 N) before the assessment of the ultimate load. To investigate the new technique further, finite element (FE) computations were conducted on the basis of the original geometry. Statistical assessment was made by the use of non-parametric tests. Initial breaking load was significantly higher in the hand-layered group than in the CAD/CAM group (mean: 1165·86 N versus 395·45 N). During chewing simulation, however, 87·5% (7/8) of the crowns in the hand-layered group failed, whereas no crown in the CAD/CAM group failed. The CAD/CAM-produced veneer was significantly less sensitive to ageing than the hand-layered veneer.
Gesehen am 12.07.2021